A silicon-containing surface modifier and anti-etching agent lower film composition and its preparation method and application
A silicon-containing surface modifier addresses the bonding issues between resist films by adjusting contact angles, ensuring uniform coating and preventing collapse, thereby improving photolithographic pattern resolution and morphology.
Patent Information
- Application Number
- CN202410003309.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-01-02
AI Technical Summary
The poor bonding effect between resist lower and upper layer films in photolithography processes leads to uneven coating and negative collapse issues, hindering the resolution and morphology of photolithographic patterns.
A silicon-containing surface modifier is introduced to enhance the adhesion between resist lower and upper films by adjusting the contact angles before and after exposure, using a specific polymerization process to create a uniform coating effect.
The silicon-containing surface modifier improves the adhesion and uniformity of the resist films, preventing negative collapse and enhancing the resolution and morphology of photolithographic patterns.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photolithographic materials, and in particular relates to a silicon-containing surface modifier, a preparation method thereof, and applications thereof in resist underlayer film compositions and photolithographic pattern formation. Background Art
[0002] The development of high integration and high speed of integrated circuits has accelerated the development of fine pattern size. These fine-tuning technologies generally involve shortening the wavelength of exposure light waves, such as KrF excimer lasers (248nm), ArF excimer lasers (193nm), and even shorter wavelength F2 excimer lasers (157nm), extreme ultraviolet lasers (EUV), electron beams, and X-rays. However, in order to achieve ultra-fine pattern lithography technology, high-resolution lithographic materials are required.
[0003] At present, the pattern forming method mainly adopts the multilayer resist method, and the three-layer resist method is commonly used, for example, an organic film is formed on the processed substrate, a resist lower layer film is formed on the organic film, and then a photoresist film is formed on the resist lower layer film as a resist upper layer film. In the prior art research, the negative developing technology utilizing the traditional positive chemical amplification photoresist material can improve the resolution. However, due to the poor bonding effect between the resist lower layer film and the resist upper layer film in the pattern forming process, the photoresist is unevenly coated and the negative collapse problem after exposure is caused. Therefore, it is necessary to find a novel surface modifier so that the resist lower layer film surface formed by using this as the raw material is closely attached to the resist upper layer film before and after exposure, thereby improving the resolution of the photoresist material, thereby obtaining a photolithographic pattern with good morphology. Summary of the Invention
[0004] One of the purposes of the present invention is to propose a method for preparing a silicon-containing surface modifier in response to the above-mentioned technical problems. The surface of the resist lower film containing the silicon-containing surface modifier is tightly adhered to the resist upper film before and after exposure, which not only has a good uniform coating effect, but also can improve the resolution of the photolithographic material.
[0005] Specifically, the preparation method of the silicon-containing surface modifier provided by the present invention comprises the following steps: n Monomer and optionally siloxane monomer S m1 It is obtained by polymerization reaction under the action of a catalyst;
[0006]
[0007] In formula (1), R1 is a structural unit having formula (M1) or (M2), at least one of R2, R3 and R4 is a C1-C5 alkoxy group and the others are independently H, C1-C5 alkyl or C6-C 18 aryl groups;
[0008]
[0009] In formula (M1) and (M2), R5 is H, C1-C6 alkyl or C6-C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents a site connected to a Si bond.
[0010] A second object of the present invention is to provide a silicon-containing surface modifier prepared by the above method.
[0011] The third object of the present invention is to provide a resist underlayer film composition, which comprises the above-mentioned silicon-containing surface modifier, polysiloxane compound, thermal crosslinking accelerator, organic acid, high boiling point solvent, water and optional photoacid generator.
[0012] A fourth object of the present invention is to provide a method for preparing the above-mentioned resist underlayer film composition, which comprises uniformly mixing a silicon-containing surface modifier, a polysiloxane compound, a thermal crosslinking accelerator, an organic acid, a high-boiling point solvent, water and an optional photoacid generator, and then filtering to obtain the resist underlayer film composition.
[0013] A fifth object of the present invention is to provide an application of the above-mentioned resist underlayer film composition in a photolithography pattern forming process.
[0014] After extensive and in-depth research, the inventors of this application found that in the negative development technology of positive photoresist materials, since the contact angles of the lower resist film and the upper resist film before and after exposure are quite different, it will not only affect the uniform coating effect, but also cause the lower resist film and the upper resist film to be unable to fit tightly, thus causing problems such as negative collapse after exposure.
[0015] The key to the present invention is to use a silicon-containing surface modifier with a specific structure and add it to the resist lower film composition in an appropriate proportion. The contact angle of the resist lower film obtained before exposure is close to the contact angle of the resist upper film, so that the photoresist has a good uniform coating effect. At the same time, the contact angle of the resist lower film after exposure is similar to that of the photoresist upper film after exposure, so that even if a negative development treatment is used, the close adhesion between the resist lower film and the photoresist pattern can be improved, thereby preventing the collapse of fine patterns and obtaining a photolithography pattern with good morphology. DETAILED DESCRIPTION
[0016] The preparation method of the silicon-containing surface modifier provided by the present invention comprises the following steps: n Monomer and optionally siloxane monomer S m1 It is obtained by polymerization reaction under the action of a catalyst;
[0017]
[0018] In formula (1), R1 is a structural unit having formula (M1) or (M2), at least one of R2, R3 and R4 is a C1-C5 alkoxy group and the others are independently H, C1-C5 alkyl or C6-C 18 The C1-C5 alkoxy group may be at least one of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentoxy, tert-pentoxy and neopentyl. The C1-C5 alkyl group may be at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl and neopentyl. The C6-C 18 The aryl group may be at least one of a phenyl group, a tolyl group, a biphenyl group, a ditolyl group, and a naphthyl group.
[0019]
[0020] In formula (M1) and (M2), R5 is H, C1-C6 alkyl or C6-C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents the site connected to the Si bond. The C1 to C6 alkyl group may be at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, isohexyl, and tert-hexyl. 18 Specific examples of the aryl group are as described above. The C1-C6 alkylene group may be at least one of methylene, ethylene, n-propylene, isopropylene, n-butylene, sec-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene, tert-pentylene, neopentylene, n-hexylene, isohexylene and tert-hexylene. The C6-C 14 The cycloalkane may be at least one of cyclohexylene, bicyclo[2,2,1]heptane, 4-methoxycyclohexylene, and 2-methoxycyclohexylene. y is an integer from 0 to 10, such as 0, 1, 2, 5, 7, 9, 10, and the like. z is an integer from 0 to 10, such as 0, 1, 2, 5, 7, 9, 10, and the like.
[0021] In the present invention, the monomer S n and siloxane monomer S m1 The molar ratio of monomer S is preferably 1: (4 to 6), n The amount of the substance is 1 mol, the siloxane monomer S m1 The molar amount is preferably 4 to 6 mol, such as 4 mol, 4.2 mol, 4.5 mol, 4.8 mol, 5 mol, 5.2 mol, 5.5 mol, 5.8 mol, 6 mol or any value therebetween.
[0022] In the present invention, the catalyst is preferably an acidic catalyst and / or a basic catalyst. The acidic catalyst may be an inorganic acid catalyst, specifically including at least one of hydrofluoric acid, hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, perchloric acid, and phosphoric acid, or an organic acid catalyst, specifically including at least one of formic acid, acetic acid, oxalic acid, maleic acid, methanesulfonic acid, benzenesulfonic acid, and toluenesulfonic acid. Specific examples of the basic catalyst include, but are not limited to, at least one of methylamine, ethylamine, propylamine, butylamine, ethylenediamine, hexamethylenediamine, dimethylamine, diethylamine, ethylmethylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, cyclohexylamine, dicyclohexylamine, monoethanolamine, diethanolamine, dimethylmonoethanolamine, monomethyldiethanolamine, triethanolamine, diazabicyclooctane, diazabicyclocyclononene, diazabicycloundecene, hexamethylenetetramine, aniline, N,N-dimethylaniline, pyridine, N,N-dimethylaminopyridine, pyrrole, piperazine, pyrrolidine, piperidine, picoline, tetramethylammonium hydroxide, choline hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, ammonia, lithium hydroxide, sodium hydroxide, potassium hydroxide, barium hydroxide, and calcium hydroxide. Relative to 1 mol of the monomer to be reacted, the amount of the catalyst used is preferably 0.005 to 0.2 mol, such as 0.005 mol, 0.008 mol, 0.01 mol, 0.05 mol, 0.1 mol, 0.15 mol, 0.2 mol or any value therebetween.
[0023] In the present invention, the siloxane monomer S m1The functionality is preferably 2 to 4, and specifically can be at least one of a difunctional siloxane monomer, a trifunctional siloxane monomer, and a tetrafunctional siloxane monomer, and specific examples thereof include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltripropoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, allyltrimethoxysilane, allyltriethoxysilane , allyltripropoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, cyclohexyltripropoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, tolyltrimethoxysilane, tolyltriethoxysilane, tolyltripropoxysilane, benzyltrimethoxysilane, benzyltriethoxysilane, benzyltripropoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, methylethyldimethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, dimethylethylmethoxysilane and dimethylphenylmethoxysilane.
[0024] In the preparation process of the silicon-containing surface modifier, the polymerization reaction temperature is preferably 40 to 60°C, such as 40°C, 42°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C and any value therebetween; the polymerization reaction time is preferably 8 to 14h, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h or any value therebetween. In a specific embodiment, the preparation method of the silicon-containing surface modifier comprises the following steps: n and optionally siloxane monomer S m1 The polymerization reaction is carried out in a solvent in the presence of a catalyst at 40-60°C for 10-18 hours. After the reaction, the reaction byproducts are removed by vacuum distillation. An organic solvent is then added to extract the silicon-containing surface modifier and the organic phase is washed. The organic phase is then concentrated by vacuum distillation to a solid content of 20-30 wt% of the silicon-containing surface modifier, and the molecular weight of the silicon-containing surface modifier is determined by gel permeation chromatography (GPC). The silicon-containing surface modifier is pre-formed into a solution with a solid content of 20-30 wt% mainly because if the silicon-containing surface modifier is too concentrated, it will further undergo condensation reaction and there is a risk that it will become insoluble in the organic solvent. If the solid content of the silicon-containing surface modifier is too low, the amount of solvent becomes excessive, which increases storage costs.
[0025] In the present invention, the number average molecular weight of the silicon-containing surface modifier is preferably 1000 to 6000 g / mol, such as 1000 g / mol, 2000 g / mol, 3000 g / mol, 4000 g / mol, 5000 g / mol, 6000 g / mol, or any value therebetween. In a specific embodiment, the number average molecular weight of the silicon-containing surface modifier can be adjusted not only by selecting the monomer, but also by controlling the reaction conditions during polymerization.
[0026] In the present invention, the S n The functionality of the monomer is preferably 1 to 3, i.e. S n The monomer has 1 to 3 siloxane groups capable of participating in the polymerization reaction. The monomer Sn is preferably prepared by condensing a compound D having a structure represented by formula (2) with a compound M having a structure represented by formula (3) and / or (4);
[0027]
[0028] In formula (2), at least one of R2, R3 and R4 is a C1-C5 alkoxy group and the others are independently H, a C1-C5 alkyl group or a C6-C 18 R1' is a structural unit having the structure shown in (D1); in (D1), R5 is H, C1-C6 alkyl or C6-C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents a site connected to Si; in formula (3) and formula (4), X is a halogen element. 18 Aryl, C1~C6 alkyl, C6~C 18 Aryl, C1~C6 alkylene and C6~C 14 The specific examples of the cycloalkanes are the same as those described above and are not described in detail here. The halogen element may be at least one of fluorine, chlorine, bromine and iodine.
[0029] Preferably, the structural unit of formula (D1) is selected from at least one of the structures shown below;
[0030]
[0031] In the above monomer S nIn the preparation process, the temperature of the condensation reaction is preferably 50-100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; the time of the condensation reaction is preferably 3-8h, such as 3h, 4h, 5h, 6h, 7h, 8h or any value therebetween. In a specific embodiment, the monomer S n The preparation method comprises the following steps: dissolving compound D in an organic solvent in a three-necked flask equipped with a magnetic stirrer, nitrogen protection and a reflux device, adding compound M to the three-necked flask at once or in 2 to 3 times, heating and refluxing at 50 to 100° C. for 3 to 8 hours, cooling to room temperature to precipitate a large amount of solid, and performing solid-liquid separation to obtain monomer S. n The molar ratio of compound D to compound M is preferably 1:(1-1.2), such as 1:1, 1:1.12, 1:1.15, 1:1.18, 1:1.2 or any value therebetween.
[0032] In the present invention, the silicon-containing surface modifier preferably contains at least one of the structures shown in formula (5), formula (6) and formula (7);
[0033]
[0034] In formula (5), formula (6) and formula (7), R1 is a structural unit having formula (M1) or (M2), R7 and R8 are each independently H, C1-C5 alkyl or C6-C 18 R' is an alkyl group of C1 to C5; in formulas (M1) and (M2), R5 is H, an alkyl group of C1 to C6 or a C6 to C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents the site connected to the Si bond. 18 Aryl, C6~C 18 Aryl, C1~C6 alkylene and C6~C 14 Specific examples of the cycloalkanes are the same as those described above.
[0035] In the present invention, the resist underlayer film composition preferably contains a silicon-containing surface modifier, a polysiloxane compound, a thermal crosslinking accelerator, an organic acid, a high boiling point solvent, water, and optionally a photoacid generator. Specifically, the mass ratio of the polysiloxane compound, the silicon-containing surface modifier, the thermal crosslinking accelerator, the organic acid, the high boiling point solvent, water, and the photoacid generator is preferably 100:(0.01-50):(0.01-30):(0.001-25):(2000-50000):(100-10000):(0.01-20). Based on the mass of the polysiloxane compound as 100 parts by weight, the mass of the silicon-containing surface modifier is preferably 0.01 to 50 parts by weight, more preferably 0.1 to 10 parts by weight, such as 0.1, 0.5, 1, 2, 5, 8, 10 parts by weight and any value therebetween; the content of the thermal crosslinking accelerator is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 15 parts by weight, such as 0.1, 0.5, 1, 2, 5, 8, 10, 12, 15 parts by weight and any value therebetween; the content of the organic acid is preferably 0.001 to 25 parts by weight, more preferably 0.01 to 15 parts by weight, such as 0.01, 0.05, 0.1, 0.5, 1, 2, 5, 8, 10, 12, 15 parts by weight and any value therebetween. any value therebetween; the content of the high boiling point solvent is preferably 2000 to 50000 parts by weight, more preferably 20000 to 40000 parts by weight, such as 20000, 25000, 30000, 35000, 40000 parts by weight or any value therebetween; the content of the water is preferably 100 to 10000 parts by weight, more preferably 500 to 5000 parts by weight, such as 500, 800, 1000, 2000, 3000, 4000, 5000 parts by weight or any value therebetween; the content of the photoacid generator is preferably 0.01 to 20 parts by weight, more preferably 0.1 to 10 parts by weight, such as 0.1, 0.5, 1, 2, 5, 8, 10 parts by weight or any value therebetween.
[0036] In the present invention, the siloxane monomer S m2 The number average molecular weight is preferably 1000 to 5000 g / mol, such as 1000, 2000, 3000, 4000, 5000 g / mol or any value therebetween. m2 The polycondensation reaction is carried out to obtain the polycondensation reaction. The temperature of the polycondensation reaction is preferably 40 to 60°C, such as 40, 42, 48, 50, 52, 55, 58, 60°C and any value therebetween. The polycondensation reaction time is preferably 10 to 18 hours, such as 10, 12, 15, 18 hours or any value therebetween. The siloxane monomer S m2It can be a trifunctional siloxane monomer or a tetrafunctional siloxane monomer. Preferably, the siloxane monomer S m2 The content of tetrafunctional monomers accounts for 1% of the total siloxane monomer S m2 The total content is preferably 50-100 wt%, such as 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 1000 wt% or any value therebetween. m2 Preferably, at least one selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltripropoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, allyltrimethoxysilane, allyltriethoxysilane, allyltripropoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, cyclohexyltripropoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, tolyltrimethoxysilane, tolyltriethoxysilane, tolyltripropoxysilane, benzyltrimethoxysilane, benzyltriethoxysilane, and benzyltripropoxysilane
[0037] In the present invention, the thermal crosslinking accelerator is preferably selected from cyclohexyl p-toluenesulfonate, 2,4,6-triisopropylbenzenesulfonate, 2-nitrobenzyl toluenesulfonate, triethylamine salt of dodecylbenzenesulfonic acid, triphenylsulfonium maleate, tetramethylammonium maleate, tetramethylammonium trifluoroacetate, tetrabutylammonium nitrate, etc.
[0038] In the present invention, the photoacid generator is preferably selected from triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium trifluoroacetate, triphenylsulfonium nonafluorobutanesulfonate, 2-nitrobenzyl-p-toluenesulfonate, 1,2,3-tris(p-toluenesulfonyloxy)benzene, and the like.
[0039] In the present invention, the organic acid is preferably selected from formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, oleic acid, stearic acid, linoleic acid, linolenic acid, benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, trifluoroacetic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, oxalic acid, malonic acid, methylmalonic acid, ethylmalonic acid, propylmalonic acid, butylmalonic acid, dimethylmalonic acid, diethylmalonic acid, succinic acid, methylsuccinic acid, glutaric acid, adipic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, citric acid, etc. In particular, at least one of oxalic acid, maleic acid, formic acid, acetic acid, propionic acid and citric acid is preferred.
[0040] In the present invention, the high boiling point solvent is preferably selected from at least one of 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, γ-butyrolactone, tripropylene glycol monomethyl ether, n-nonyl acetate, ethylene glycol ethyl ether acetate, 1,2-diacetoxypropane, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monobutyl ether acetate and dipropylene glycol monomethyl ether acetate.
[0041] In the present invention, the preparation method of the resist underlayer film composition preferably includes mixing a silicon-containing surface modifier, a polysiloxane compound, a thermal crosslinking accelerator, an organic acid, a high-boiling point solvent, water and an optional photoacid generator and then filtering to obtain the resist underlayer film composition.
[0042] In the present invention, the resist underlayer film composition can be used in a photolithographic pattern formation process. In a specific embodiment, the photolithographic pattern formation process includes: forming an organic underlayer film on a substrate to be processed using a spin-coated organic underlayer film material, forming a resist underlayer film on the organic underlayer film using the resist underlayer film composition, and forming a photoresist upper film on the resist underlayer film using a chemically amplified photoresist composition; exposing the photoresist upper film to high-energy radiation after a heat treatment, dissolving the unexposed portion of the photoresist upper film using an organic solvent developer to form a negative pattern, transferring the negative pattern to the resist underlayer film by etching using the photoresist upper film printed with the negative pattern as a mask, transferring the negative pattern to the organic film underlayer film by etching using the resist underlayer film printed with the negative pattern as a mask, and then transferring the pattern to the substrate to be processed by etching using the organic film underlayer film printed with the negative pattern as a mask. In addition, a hard mask with carbon as the main component can be formed on the processed substrate using the CVD method, and the remaining steps are consistent with the above method.
[0043] The present invention will be described in detail below through specific examples.
[0044] Preparation Example 1 Monomer S n Preparation of -1
[0045] In a three-necked flask equipped with magnetic stirring, nitrogen protection and reflux device, 22.2g (0.1mol) of 3-(triethoxysilyl)propan-1-ol was dissolved in 250mL of tetrahydrofuran, and then 28.8g (0.106mol) of 3-diazo-4-oxy-3,4-dihydro-1-naphthalenesulfonyl chloride was added to the three-necked flask in two portions. The mixture was slowly added to reflux and heated under reflux at 70°C for 5h. The system was then cooled to room temperature. A large amount of solid precipitated, which was filtered and the filter cake was rinsed with a small amount of tetrahydrofuran. After vacuum drying, 33.6g of light yellow product was obtained with a yield of 74%.
[0046] The specific preparation process is as follows.
[0047]
[0048] Preparation Example 2 Monomer S n Preparation of -2
[0049] In a three-necked flask equipped with magnetic stirring, nitrogen protection and reflux device, 22.2g (0.1mol) of 3-(triethoxysilyl)propan-1-ol was dissolved in 250mL of tetrahydrofuran, and then 28.8g (0.106mol) of 6-diazo-5,6-dihydro-5-oxo-1-naphthalenesulfonyl chloride was added to the three-necked flask in two portions. The mixture was slowly added to reflux and heated under reflux at 70°C for 5h. The system was then cooled to room temperature. A large amount of solid precipitated, which was filtered and the filter cake was rinsed with a small amount of tetrahydrofuran. After vacuum drying, 28.2g of light yellow product was obtained with a yield of 62%.
[0050] The specific preparation process is as follows.
[0051]
[0052] Preparation Example 3 Monomer S n Preparation of -3
[0053] In a three-necked flask equipped with magnetic stirring, nitrogen protection and reflux device, 22.8g (0.1mol) of phenyl(trimethoxysilyl)methanol was dissolved in 250mL of tetrahydrofuran, and then 28.8g (0.106mol) of 3-diazo-4-oxy-3,4-dihydro-1-naphthalenesulfonyl chloride was added to the three-necked flask in two portions. The mixture was slowly added to reflux and heated under reflux at 70°C for 5h. The system was then cooled to room temperature. A large amount of solid precipitated, which was filtered and the filter cake was rinsed with a small amount of tetrahydrofuran. After vacuum drying, 29.4g of light yellow product was obtained with a yield of 64%.
[0054] The specific preparation process is as follows.
[0055]
[0056] Preparation Example 4 Monomer S n Preparation of -4
[0057] In a three-necked flask equipped with magnetic stirring, nitrogen protection, and reflux, 24.8 g (0.1 mol) of 4-(2-(trimethoxysilyl)ethyl)cyclohexane-1-ol was dissolved in 250 mL of tetrahydrofuran. 28.8 g (0.106 mol) of 6-diazo-5,6-dihydro-5-oxo-1-naphthalenesulfonyl chloride was then added to the flask in two portions. The mixture was slowly added until refluxed. The mixture was heated at 70°C for 5 h and then cooled to room temperature. A large amount of solid precipitated. The filter cake was filtered and rinsed with a small amount of tetrahydrofuran. After vacuum drying, 34.1 g of a light yellow product was obtained with a yield of 71%. The specific preparation process is shown below.
[0058]
[0059] Preparation Example 5 Preparation of polysiloxane compound B-1
[0060] 20 g of siloxane monomer S was added to a system of 120 g of methanol, 0.1 g of 70% nitric acid and 65 g of deionized water. m1 -1 (tetramethoxysilane), 15g siloxane monomer S m1 -2 (methyltrimethoxysilane) and 3g siloxane monomer S m1 -3 (phenyltrimethoxysilane), heating the system to 50 ° C and maintaining for 14 hours to hydrolyze the monomer and perform polycondensation; after the reaction is completed, 100 g of propylene glycol ethyl ether (PGEE) is added, and the methanol is removed by distillation under reduced pressure. Then, 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether are added, and the water layer is removed by separation; then, 100 g of deionized water is added to the organic phase, and the organic phase is washed by stirring, standing, and separation. The organic phase is then concentrated by distillation under reduced pressure to a solid content of the silicon-containing polymer of 25 wt%, to obtain a polysiloxane compound B-1, and its molecular weight is measured by GPC, Mw = 3080 g / mol.
[0061] Preparation Example 6 Preparation of polysiloxane compound B-2
[0062] 20 g of siloxane monomer S was added to a system of 120 g of methanol, 0.1 g of 70% nitric acid and 70 g of deionized water. m1 -1 (tetramethoxysilane), 12g siloxane monomer S m1 -2 (methyltrimethoxysilane) and 6g siloxane monomer S m1-3 (phenyltrimethoxysilane), heating the system to 50 ° C and maintaining for 14 hours to hydrolyze the monomer and perform polycondensation; after the reaction is completed, 100 g of propylene glycol ethyl ether (PGEE) is added, and the methanol is removed by distillation under reduced pressure. Then, 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether are added, and the water layer is removed by separation; then, 100 g of deionized water is added to the organic phase, and the organic phase is washed by stirring, standing, and separation. The organic phase is then concentrated by distillation under reduced pressure to a solid content of the silicon-containing polymer of 25 wt%, to obtain a polysiloxane compound B-2, and its molecular weight is measured by GPC, Mw = 3180 g / mol.
[0063] Example 1 Preparation of Silicon-Containing Surface Modifier A-1
[0064] 22 g of siloxane monomer S was added to a system of 90 g of methanol, 0.1 g of 70% nitric acid and 55 g of deionized water. m1 -1 (tetramethoxysilane) and 13g monomer S n -1, heated to 50°C and maintained for 14 hours to hydrolyze the monomer and undergo polycondensation; after the reaction, 100 g of propylene glycol ethyl ether (PGEE) was added, and the methanol was removed by distillation under reduced pressure. Then, 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether were added, and the water layer was removed by separation; then, 100 g of deionized water was added to the organic phase, and the organic phase was washed by stirring, standing, and separation, and then the organic phase was concentrated by distillation under reduced pressure to a solid content of the silicon-containing polymer of 25 wt%, thereby obtaining a silicon-containing surface modifier A-1, and its molecular weight was measured by GPC, Mw = 2550 g / mol.
[0065] Example 2 Preparation of Silicon-Containing Surface Modifier A-2
[0066] 22 g of siloxane monomer S was added to a system of 90 g of methanol, 0.1 g of 70% nitric acid and 55 g of deionized water. m1 -1 (tetramethoxysilane) and 13g monomer S n -2, heating the system to 50°C and maintaining it for 14 hours to hydrolyze the monomers and undergo polycondensation; after the reaction, adding 100 g of propylene glycol ethyl ether, removing the methanol by vacuum distillation, then adding 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether, and removing the aqueous layer by separation; then adding 100 g of deionized water to the organic phase, stirring, allowing it to stand, and separating the organic phase to wash it, and then concentrating the organic phase by vacuum distillation to a solid content of 25 wt % of the silicon-containing polymer. The molecular weight was determined by GPC to obtain silicon-containing surface modifier A-2, which had a molecular weight of 2710 g / mol.
[0067] Example 3 Preparation of Silicon-Containing Surface Modifier A-3
[0068] 28 g of siloxane monomer S was added to a system of 120 g of ethanol, 14 g of 25% tetramethylammonium hydroxide and 55 g of deionized water. m1 -1 (tetramethoxysilane) and 16g monomer S n -3, heated to 60 ° C and maintained for 8 hours to hydrolyze the monomer and undergo polycondensation, acetic acid was added to neutralize the system, and then ethanol was removed by distillation under reduced pressure, and then 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether were added, and the water layer was removed by separation; then 100 g of deionized water was added to the organic phase, and the organic phase was washed by stirring, standing, and separation, and then the organic phase was concentrated by distillation under reduced pressure to a solid content of the silicon-containing polymer of 25 wt%, to obtain a silicon-containing surface modifier A-3, and its molecular weight was measured by GPC, Mw = 2840 g / mol.
[0069] Example 4 Preparation of Silicon-Containing Surface Modifier A-4
[0070] 23 g of siloxane monomer S was added to a system of 120 g of ethanol, 14 g of 25% tetramethylammonium hydroxide and 55 g of deionized water. m1 -2 (methyltrimethoxysilane) and 16g monomer S n -4, heated to 60°C and maintained for 8 hours to hydrolyze the monomer and undergo polycondensation; acetic acid was added to neutralize the system, and then ethanol was removed by vacuum distillation, followed by the addition of 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether, and the aqueous layer was removed by liquid separation; then 100 g of deionized water was added to the organic phase, and the organic phase was washed by stirring, standing, and liquid separation, and then the organic phase was concentrated by vacuum distillation to a solid content of the silicon-containing polymer of 25 wt%, thereby obtaining a silicon-containing surface modifier A-4, the molecular weight of which was determined by GPC, Mw = 2570 g / mol.
[0071] Example 5 Preparation of Silicon-Containing Surface Modifier A-5
[0072] 16 g of siloxane monomer S was added to a system of 90 g of methanol, 0.1 g of 70% nitric acid and 55 g of deionized water. m1 -1 (tetramethoxysilane), 8g siloxane monomer S m1 -2 (methyltrimethoxysilane) and 13g monomer S n-1, heated to 50°C and maintained for 14 hours to hydrolyze the monomer and undergo polycondensation; after the reaction, 100 g of propylene glycol ethyl ether was added, methanol was removed by vacuum distillation, 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether were added, and the water layer was removed by liquid separation; then 100 g of deionized water was added to the organic phase, and the organic phase was washed by stirring, standing, and liquid separation, and then the organic phase was concentrated by vacuum distillation to a solid content of the silicon-containing polymer of 25 wt%, to obtain a silicon-containing surface modifier A-5, and its molecular weight was measured by GPC, Mw = 3080 g / mol.
[0073] Example 6 Preparation of Silicon-Containing Surface Modifier A-6
[0074] 22g of siloxane monomer S was added to a system of 120g of ethanol, 14g of 25% tetramethylammonium hydroxide and 55g of deionized water. m1 -1 (tetramethoxysilane), 8g siloxane monomer S m1 -2 (methyltrimethoxysilane) and 16g monomer S n -3, heated to 60°C and maintained for 8 hours to hydrolyze the monomer and undergo polycondensation; acetic acid was added to neutralize the system, and then ethanol was removed by distillation under reduced pressure, followed by the addition of 600 ml of ethyl acetate and 100 g of propylene glycol ethyl ether, and the aqueous layer was removed by separation; then 100 g of deionized water was added to the organic phase, and the organic phase was washed by stirring, standing, and separation, and then the organic phase was concentrated by distillation under reduced pressure to a solid content of the silicon-containing polymer of 25 wt%, to obtain a silicon-containing surface modifier A-6, the molecular weight of which was determined by GPC, Mw = 2910 g / mol.
[0075] Preparation of Resist Underlayer Film Compositions of Examples 7-14 and Comparative Examples 1-2
[0076] The silicon-containing surface modifiers A-1 to A-6 prepared in the above examples, the polysiloxane compounds B-1 to B-2 synthesized in the above preparation examples, a thermal crosslinking accelerator, a photoacid generator, an organic acid, a high-boiling point solvent and water were uniformly mixed in the proportions shown in Table 1, and then filtered through a 0.1 μm fluororesin filter to obtain the resist underlayer film compositions of Examples 7 to 14 (named S1 to S8) and the reference resist underlayer film compositions of Comparative Examples 1 to 2 (named R1 to R2).
[0077] Table 1
[0078]
[0079]
[0080] The thermal crosslinking accelerator includes triphenylmercapto maleate (TPSMA) and triphenylmercapto trifluoroacetate (TPSTFA), the photoacid generator is triphenylmercapto nonafluorobutanesulfonate (TPSNf), and the high boiling point solvent is propylene glycol ethyl ether.
[0081] Test Case
[0082] (1) Contact angle test
[0083] a. Contact angle test of the photoresist upper film before and after exposure
[0084] The argon fluoride photoresist solutions (PR1 and PR2) for negative development listed in Table 2 were spin-coated onto silicon wafers and baked at 100°C for 60 seconds to produce 110nm thick photoresist top layers. The contact angles with pure water were then measured. The same photoresist films were then exposed in an argon fluoride exposure system (ASML1900), baked at 100°C for 60 seconds (PEB), rinsed with diisoamyl ether, spin-dried, and baked at 100°C for 20 seconds to evaporate the rinse solvent. This produced an argon fluoride photoresist film corresponding to the pattern portion where the acid-leaving groups had been removed during negative development. The contact angles with pure water were then measured. The results are shown in Table 3.
[0085] Table 2
[0086]
[0087] Table 3
[0088]
[0089]
[0090] Among them, the molecular weight Mw of argon fluoride photoresist polymer 1 is 14000 g / mol, the dispersity (Mw / Mn) is 1.8, and it has a molecular structure shown in formula (I); the molecular weight Mw of argon fluoride photoresist polymer 2 is 1000 g / mol, the dispersity (Mw / Mn) is 1.7, and it has a molecular structure shown in formula (II); the acid generator is triphenylsulfonium nonafluorobutanesulfonate, which has a molecular structure shown in formula (III); and the base is triethanolamine, which has a molecular structure shown in formula (IV).
[0091]
[0092] b. Contact angle test of the lower layer of the resist before exposure
[0093] The anti-etching agent lower layer film compositions S1 to S8 and R1 to R2 were spin-coated on a silicon wafer and heated at 240°C for 60 seconds to produce silicon-containing films Film1 to Film10 with a film thickness of 38 nm. The contact angle (CA1) with pure water was measured. The results are shown in Table 4.
[0094] Table 4
[0095] Sample number Contact angle (CA1) Sample number Contact angle (CA1) S1-Film1 70° S6-Film6 72° S2-Film2 72° S7-Film7 70° S3-Film3 71° S8-Film8 71° S4-Film4 72° R1-Film9 66° S5-Film5 70° R2-Film10 65°
[0096] c. Contact angle test of the lower layer of the anti-reagent film after exposure
[0097] The resist underlayer film compositions S1 to S8 and R1 to R2 were spin-coated on a silicon wafer and heated at 240°C for 60 seconds to form silicon-containing films Film1 to Film10 with a thickness of 38 nm. The argon fluoride photoresist solution (PR1) for negative development described in Table 2 was spin-coated thereon and baked at 100°C for 60 seconds to form a photoresist upper film with a thickness of 110 nm. The wetting protective film (TC-1) described in Table 5 was then applied on the photoresist film and baked at 90°C for 60 seconds to form a protective film with a thickness of 50 nm. The multilayer film composition was then exposed in an argon fluoride exposure apparatus (ASML1900), baked (PEB) at 100°C for 60 seconds, developed using ethyl acetate as a developer for 30 seconds, rinsed with diisoamyl ether, and spin-dried. The film was then baked at 100°C for 20 seconds to evaporate the rinsing solvent. The remaining photoresist film was completely removed by rinsing with PGME to obtain an exposed resist underlayer film. The contact angle (CA2) with pure water was measured. The results are shown in Table 5.
[0098] Table 5
[0099] Sample number Contact angle (CA2) Sample number Contact angle (CA2) S1-Film1 52° S6-Film6 54° S2-Film2 51° S7-Film7 52° S3-Film3 53° S8-Film8 51° S4-Film4 50° R1-Film9 66° S5-Film5 53° R2-Film10 65°
[0100] Among them, the wetting protective film (TC-1) includes 100 parts by weight of a protective film polymer, 2700 parts by weight of diisoamyl ether and 270 parts by weight of 2-methyl-1-butanol. The molecular weight Mw of the protective film polymer is 8800 g / mol, the dispersion (Mw / Mn) is 1.69, and it has a molecular structure shown in formula (V).
[0101]
[0102] (2) Glue spreading effect test
[0103] A spin-on carbon film LSOH-0200 with a thickness of 200 nm was formed on a silicon wafer, and resist underlayer film compositions S1 to S8 and R1 to R2 were spin-coated thereon. The films were heated at 240°C for 60 seconds to produce resist underlayer films Film1 to Film10 with a thickness of 38 nm. An argon fluoride photoresist solution (PR-1) was then spin-coated on the resist underlayer films and baked at 100°C for 60 seconds to form a photoresist upper film with a thickness of 110 nm. The film formation effect was observed, and the difference between the contact angle (CAPR1-1) of the photoresist upper film (PR-1) before exposure and the contact angle (CA1) of the resist underlayer film was calculated. The results are shown in Table 6.
[0104] Table 6
[0105]
[0106] As can be seen from Table 6, the silicon-containing surface modifier provided by the present invention and the resist lower film obtained using the same as the raw material have a contact angle difference of less than 5° with the photoresist upper film before exposure, thereby achieving good leveling effect when forming a photoresist coating on the resist lower film. In addition, the resist lower film and the photoresist upper film are tightly adhered to each other, which is beneficial for ensuring that the developed pattern does not collapse and obtaining a photolithographic pattern with good morphology.
[0107] (3) Patterning effect test using negative development
[0108] A 200nm thick spin-on carbon film LSOH-0200 was formed on a silicon wafer. Resist underlayer film compositions S1-S8 and R1-R2 were spin-coated thereon and heated at 240°C for 60 seconds to form 38nm thick resist underlayer films Film1-Film10. An argon fluoride photoresist solution (PR1) for negative development was then spin-coated on the resist underlayer film and baked at 100°C for 60 seconds to form a 110nm thick photoresist top layer. The multilayer film composition was then exposed using an argon fluoride exposure system (ASML1900), baked at 100°C for 60 seconds (PEB), and developed for 30 seconds using butyl acetate as a developer. After rinsing with diisoamyl ether, the film was spin-dried and baked at 100°C for 20 seconds to evaporate the rinsing solvent. Thus, a 45nm 1:1 negative line and space pattern was obtained, and its size was measured using a Hitachi High-Technologies Corporation electron microscope (CG6300). The pattern collapse and cross-sectional shape were measured using an electron microscope (S-4700 manufactured by Hitachi), and the difference between the contact angle (CAPR1-2) of the lower layer of the photoresist film after exposure and the contact angle (CA2) of the upper layer of the photoresist film was calculated. The results are shown in Table 7.
[0109] Table 7
[0110]
[0111] As shown in Table 7, the difference in contact angle between the resist lower layer provided by the present invention and the photoresist upper layer after exposure is less than 5°, indicating that the resist lower layer and the photoresist upper layer are tightly adhered to each other after exposure. This helps improve the resolution of the photoresist material and ensures that the photoresist pattern does not collapse during the transfer process from the photoresist upper layer to the resist lower layer, thereby obtaining a photoresist pattern with fine size and good morphology.
[0112] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A method for preparing a silicon-containing surface modifier, characterized in that: The preparation method comprises the following steps: n Monomers and siloxane monomers S m1 The siloxane monomer S is obtained by polymerization reaction under the action of a catalyst; m1 The functionality is 2~4; Formula (1), In formula (1), R1 is a group having a structure as shown in formula (M1) or (M2), and R2, R3 and R4 are all C1-C5 alkoxy groups; <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (M1)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (M2) In formula (M1) and (M2), R5 is H, C1~C6 alkyl or C6~C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents the site connected to the Si bond.
2. The method for preparing a silicon-containing surface modifier according to claim 1, characterized in that: The monomer S n and siloxane monomer S m1 The molar ratio is 1:(4~6).
3. The method for preparing a silicon-containing surface modifier according to claim 1, characterized in that: The catalyst is an acidic catalyst and / or a basic catalyst.
4. The method for preparing a silicon-containing surface modifier according to claim 1, characterized in that: The siloxane monomer S m1 Selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltripropoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, allyltrimethoxysilane, allyltriethoxysilane, allyltripropoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, At least one of cyclohexyltripropoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, tolyltrimethoxysilane, tolyltriethoxysilane, tolyltripropoxysilane, benzyltrimethoxysilane, benzyltriethoxysilane, benzyltripropoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, methylethyldimethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, dimethylethylmethoxysilane and dimethylphenylmethoxysilane.
5. The method for preparing a silicon-containing surface modifier according to claim 1, characterized in that: The monomer Sn is prepared by condensing a compound D having a structure represented by formula (2) with a compound M having a structure represented by formula (3) and / or (4); Formula (2), (D1), Formula (3), Formula (4), In formula (2), at least one of R2, R3 and R4 is a C1-C5 alkoxy group and the others are independently H, a C1-C5 alkyl group or a C6-C 18 An aryl group, R1' is a structural unit having a structure as shown in (D1); In (D1), R5 is H, C1~C6 alkyl or C6~C 18 R6 is C1~C6 alkylene or C6~C 14 Cycloalkane, y is an integer from 0 to 10, z is an integer from 0 to 10, (Si) represents the site connected to the Si bond; In formula (3) and formula (4), X is a halogen element.
6. The method for preparing a silicon-containing surface modifier according to claim 5, characterized in that: The molar ratio of the compound D to the compound M is 1:(1-1.2).
7. A silicon-containing surface modifier prepared by the method described in any one of claims 1 to 6.
8. The silicon-containing surface modifier according to claim 7, characterized in that The silicon-containing surface modifier contains a structure as shown in formula (7); Formula (7), <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (M1)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (M2) In formula (7), R1 is a group having a structure as shown in formula (M1) or (M2), and R' is a C1-C5 alkyl group; in formula (M1) and (M2), R5 is H, a C1-C6 alkyl group or a C6-C 18 R6 is C1~C6 alkylene or C6~C 14 wherein y is an integer from 0 to 10, z is an integer from 0 to 10, and (Si) represents the site connected to the Si bond.
9. The silicon-containing surface modifier according to claim 7, characterized in that The number average molecular weight of the silicon-containing surface modifier is 1000-6000 g / mol.
10. A resist underlayer film composition, characterized in that: The resist underlayer film composition contains the silicon-containing surface modifier according to any one of claims 7 to 9, a polysiloxane compound, a thermal crosslinking accelerator, an organic acid, a high boiling point solvent, water, and optionally a photoacid generator.
11. The resist underlayer film composition according to claim 10, characterized in that The mass ratio of the polysiloxane compound, the silicon-containing surface modifier, the thermal crosslinking accelerator, the organic acid, the high boiling point solvent, water and the photoacid generator is 100:(0.01-50):(0.01-30):(0.001-25):(2000-50000):(100-10000):(0.01-20).
12. The resist underlayer film composition according to claim 10, characterized in that The polysiloxane compound is prepared by mixing siloxane monomer S m2 Obtained by polycondensation reaction.
13. The resist underlayer film composition according to claim 10, characterized in that The siloxane monomer S m2 The number average molecular weight is 1000~5000g / mol.
14. The resist underlayer film composition according to claim 10, characterized in that The siloxane monomer S m2 The functionality is 3~4.
15. The resist underlayer film composition according to claim 10, characterized in that The siloxane monomer S m2 At least one selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltripropoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, allyltrimethoxysilane, allyltriethoxysilane, allyltripropoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, cyclohexyltripropoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, tolyltrimethoxysilane, tolyltriethoxysilane, tolyltripropoxysilane, benzyltrimethoxysilane, benzyltriethoxysilane and benzyltripropoxysilane.
16. The resist underlayer film composition according to claim 10, characterized in that The siloxane monomer S m2 The content of tetrafunctional monomers accounts for 1.3% of siloxane monomers S m2 The total content ratio is 50~100wt%.
17. The method for preparing a resist underlayer film composition according to any one of claims 10 to 16, characterized in that: The preparation method comprises the steps of uniformly mixing a silicon-containing surface modifier, a polysiloxane compound, a thermal crosslinking accelerator, an organic acid, a high boiling point solvent, water and an optional photoacid generator, and then filtering the mixture to obtain a resist lower layer film composition.
18. Use of the resist underlayer film composition according to any one of claims 10 to 16 in a photolithography pattern formation process.
Citation Information
Patent Citations
Lithography resist underlayer film-forming-composition containing hydrolyzable silane having carbonate skeleton
CN107209460A
Alkaline developer soluable silicon-containing resist underlayer film-forming composition
CN110809739A
Positive radiosensitive resin composition
CN110998442A
Silicon-containing resist under film forming composition and pattern forming method
CN114594657A
Positive photosensitive polybenzoxazole resin composition as well as preparation method and application thereof
CN115047715A
